(untitled) (Indian Journal of Experimental Biology (IJEB), 2022)
Thyroid cancer, known to be common in women than men, accounts for 12% all types of cancers and ranks 9th with5,86,202 cases worldwide. Role of forkhead box A1 (FOXA1), also known as hepatocyte nuclear factor 3α and involved inthe oncogenesis and progression of several tumors such as gliomas, breast, stomach, lung, ovarian, and esophageal cancers,has not been elucidated well in thyroid carcinoma until now. Here, we analyzed the expression of FOXA1 in thyroidcarcinoma tissues and its effects on the biological characteristics of papillary thyroid carcinoma TPC-1 cells. The expressionlevels of FOXA1 in normal thyroid and thyroid carcinoma tissues were analyzed using UALCAN database(http://ualcan.path.uab.edu/index.html), and the correlations between FOXA1 expression levels and survival time of patientswith thyroid carcinoma were analyzed. Si-FOXA1 and si-NC were transfected into cells that were then divided into si-FOXA1 (transfected si-FOXA1), si-NC (transfected si-NC), and control (TPC-1) groups. Cell proliferation was determinedwith MTT assay, and invasion ability was measured by Transwell assay. Early apoptotic rate was detected by flowcytometry. The mRNA expression levels of p27Kip1, Cyclin D1 and Cyclin E were measured by qRT-PCR. The expressionlevel of FOXA1 was significantly higher in thyroid carcinoma tissues than that in normal thyroid tissues. UALCAN-basedanalysis indicated that patients with low expression level of FOXA1 had longer survival time than those with highexpression level of FOXA1 (P <0.05). The cell proliferation rate was significantly lower in si-FOXA1 group than those insi-NC group and control group at 24 h, 48 h and 72 h (P <0.05). The early apoptotic rate was significantly higher andnumber of invading cells was lower in si-FOXA1 group than those in si-NC and control groups (P <0.05). Si-FOXA1 grouphad higher mRNA expression level of p27Kip1 and lower expression levels of Cyclin D1 and Cyclin E than those of si-NCand control groups (P <0.05). Targeted inhibition of FOXA1 suppresses the proliferation and invasion and promotes theapoptosis of thyroid carcinoma cells, probably by regulating activation of the p27Kip1 pathway.